1984
DOI: 10.1002/app.1984.070290111
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical degradation of acetylated, methylated, phenylhydrazine-modified, and ACC-treated wood

Abstract: SynopsisIf wood under clear, ultraviolet-transparent coatings could be protected from photodegradation, the performance of clear finishes would be greatly enhanced. The objective of this study was to determine whether acetylation or methylation of the wood and whether reaction with phenylhydrazine or treatment with acid copper chromate would impart resistance to photodegradation by longwave UV light. Infrared (IR) and ultraviolet (UV) spectra, analysis of wood before and after irradiation, and quantitative det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 4 publications
2
8
0
1
Order By: Relevance
“…Plackett et al (1992) reported reduced colour change and surface checking of acetylated Pinus radiata on accelerated weathering. Kalnins (1984), however, found that irradiation of acetylated redwood produced increased quantities of carbon dioxide, carbon monoxide, methanol and formaldehyde compared with untreated wood. Kalnins concluded that acetyl groups were resistant to photodegradation but that acetylation made the rest of the wood more susceptible to photodegradation.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Plackett et al (1992) reported reduced colour change and surface checking of acetylated Pinus radiata on accelerated weathering. Kalnins (1984), however, found that irradiation of acetylated redwood produced increased quantities of carbon dioxide, carbon monoxide, methanol and formaldehyde compared with untreated wood. Kalnins concluded that acetyl groups were resistant to photodegradation but that acetylation made the rest of the wood more susceptible to photodegradation.…”
Section: Introductionmentioning
confidence: 91%
“…Kalnins (1984) reported that irradiation of acetylated redwood produced increased quantities of volatile products such as carbon dioxide, carbon monoxide, formaldehyde and methanol compared with extracted wood. He also reported, however, that the acetyl groups themselves were resistant to photodegradation.…”
Section: (Is) Peak Areasmentioning
confidence: 99%
“…However, acetylated wood only shows initial stability against UV radiation; later, it begins to fade and grey (Kalnins 1984, Hon 1995, Torr et al 1996, Ota et al 1996, 1997, Ohkoshi 2002, Mitsui -Tolvaj 2004, 2005. This is also true for Accoya® Radiata pine (Meyer 2006, Lahtela -Kärki 2015.…”
Section: Introductionmentioning
confidence: 97%
“…Subsequently, photoyellowing of the wood surfaces occurs, and lignin degradation leads to the loss of integrity of the wood surface structure. However, photooxi-dation of acetylated wood had also been observed (Feist et al 1991;Kalnins 1984;Kiguchi 1997;Chang and Chang 1999). Chemical modification has been used to protect wood from environmental degradation (Kumar 1994).…”
Section: Introductionmentioning
confidence: 98%